Probiotics - A broad spectrum therapy - DJ, Mukesh Kumar; Roy, Nilam; Kuila, Shuvendu Kumar; PT, Kalaichelvan (Journal of Research in Biology, 2012)
“Probiotics” are the living microorganisms which are healthful to the human population. In recent years, these probiotics are being universally used in the doctoring of broad range of human diseases, conditions and syndromes. Various researches and clinical trials have been carried out for the proper annotation of the mechanisms and their mode of action which they exert on human health. Strong evidences substantiate the efficient use of probiotics in the treatment and prevention of Candidiasis, hypercholesterolemia, diarrhoea, dermatitis and several other diseases. The probiotic agents which are most commonly used are lactobacillus, bifidobacterium, and yeast. In this review, detailed overview of the use of these probiotic agents were done for curing several ailments with manifestations of clinical trials. In future, probiotics could be used as a remedy for colon and bladder cancer, diabetes, and rheumotoid arthiritis